Asignaturas de psicología experimental en las mallas curriculares de las escuelas profesionales de psicología en universidades peruanas - Torres Marrufo, Diego (2026)
The main objective was to identify the state of and institutional interest in experimental psychology in Peru, taking into account the number of courses included in the curricula of universities with current licenses. The method used was the collection of publicly available information from each university’s website in the curriculum section, up to December 2024. The results generally showed that most schools belong to the health sciences and that up to 43% of the total undergraduate offerings include at least one course in experimental psychology, with the majority offered by schools outside the capital. It is concluded that experimental psychology is underrepresented in the curricula of different schools and faculties across the country, in contrast to other professional subjects. Despite the foundational nature of psychology as a scientific discipline, currently in Peru, 6 out of 10 students studying this field will not have the opportunity to learn about experimental practices for the study of behavior.